Peran Media Digital dalam Komunikasi Kebencanaan: Antara Kecepatan Informasi dan Akurasi Pesan - Muhammad Rasyad Ghazali Saraan (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2026)
Indonesia is a country with a high level of disaster vulnerability due to its geographical and geological conditions, making disaster communication a crucial factor in disaster risk reduction. The development of digital media has transformed disaster communication practices by enabling rapid information dissemination, wide reach, and interactive communication. However, these advantages are not always accompanied by accurate and consistent message management, which may lead to misinformation, public panic, and poor decision-making. This article aims to analyze the role of digital media in disaster communication, identify key challenges in digital disaster communication, and propose directions for developing more effective and trust-based communication strategies. This study employs a qualitative descriptive approach through literature review, analysis of disaster-related documents, and case studies in Palu–Donggala, Lombok, and coastal Aceh. The findings indicate that weak coordination among communication actors, inconsistent official messaging, low public media literacy, and the dominance of informal information sources in digital spaces are the main factors undermining the effectiveness of disaster communication. These results highlight the need to manage